2018
DOI: 10.3389/fimmu.2018.02993
|View full text |Cite
|
Sign up to set email alerts
|

Using Dendritic Cell-Based Immunotherapy to Treat HIV: How Can This Strategy be Improved?

Abstract: Harnessing dendritic cells (DC) to treat HIV infection is considered a key strategy to improve anti-HIV treatment and promote the discovery of functional or sterilizing cures. Although this strategy represents a promising approach, the results of currently published trials suggest that opportunities to optimize its performance still exist. In addition to the genetic and clinical characteristics of patients, the efficacy of DC-based immunotherapy depends on the quality of the vaccine product, which is composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 108 publications
(139 reference statements)
0
20
0
1
Order By: Relevance
“…Despite meeting the conservation criteria, several short stretches of Env were excluded from our Ultra Conserved design, because of past associations with Env CD8+ T-cell responses and poor viral control, 18,73,74 as well as for the practical reason that excluding Env would enable sequencing to be restricted to the 5' half of the genome in future clinical studies (Figure 1). This design is currently being evaluated in a dendritic-cell-based vaccination strategy (NCT03758625), 75,76 which obviates the need to concatenate epitopes into polypeptide strings in a therapeutic setting. 69,71 An additional novel alternative approach for CD8 + T-cell vaccine design proposes a selection of regions for inclusion informed by structure-based network analysis, which identifies the regions of the highest importance to HIV-1 protein tertiary and quaternary structure.…”
Section: Vaccine-induced Cd8+ T-cells Responses Associated With Protementioning
confidence: 99%
“…Despite meeting the conservation criteria, several short stretches of Env were excluded from our Ultra Conserved design, because of past associations with Env CD8+ T-cell responses and poor viral control, 18,73,74 as well as for the practical reason that excluding Env would enable sequencing to be restricted to the 5' half of the genome in future clinical studies (Figure 1). This design is currently being evaluated in a dendritic-cell-based vaccination strategy (NCT03758625), 75,76 which obviates the need to concatenate epitopes into polypeptide strings in a therapeutic setting. 69,71 An additional novel alternative approach for CD8 + T-cell vaccine design proposes a selection of regions for inclusion informed by structure-based network analysis, which identifies the regions of the highest importance to HIV-1 protein tertiary and quaternary structure.…”
Section: Vaccine-induced Cd8+ T-cells Responses Associated With Protementioning
confidence: 99%
“…These results suggested that antigen-loaded DCs could be a promising therapeutic vaccine strategy to induce anti-viral responses and antigen-specific protective immune responses in HIV-infected individuals. Subsequently, many phase I clinical trials were evaluated to confirm the safety of DC inoculations, and phase II trials have investigated the therapeutic efficacy of the DC vaccines in HIV-1 infected patients [89,[96][97][98].…”
Section: Roles Of Dcs In Therapeutic Hiv Vaccinesmentioning
confidence: 99%
“…HIV evades innate immune sensing by the DCs, which leads to inefficient maturation and results in a weak adaptive immune response [23]. Therefore, the sensitized DC administration might drive the immune response to the desired specific target and improve anti-HIV-specific response [24]. Various strategies, mostly with autologous DCs obtained from patients were conducted, in which the DCs were loaded with plasma-derived target antigens followed by giving back to the sample donor [25].…”
Section: Introductionmentioning
confidence: 99%
“…This trial assessed the safety and efficiency of dendritic cell administration as a therapeutic vaccine in infected individuals. For doing this, ex-vivo generated DCs were loaded with HIV-1 lipopeptides comprising five HIV-1-antigen peptides [Gag (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), Gag (253-284), Nef (66-97), Nef (116-145), Pol (325-355)] and an Analytical Treatment Interruption (ATI) was conducted on the vaccine recipients at the week 24. The regimen was well-tolerated and elicited polyfunctional HIV-specific responses, but the virus rebound was observed after 14 days [33].…”
Section: Introductionmentioning
confidence: 99%